Interleaver Optimal Turbo Code pada Kanal Flat Fading - Kuswanto, Dwi (Rekayasa, 2009)
Turbo Code is one of the channel encoding technique used in wireless cellular networks are approaching  the limit of Shannon's  theory. Interleaver  is used  to determine  the rules of the randomization technique of bits of information in relation to the performance  of the Tubo code. Therefore, the design needs a good interleaver structure. In this paper, analyzed the performance Turbo Codefor variations interleaver structure and sizes in relation to bzt error rate (bit error rate). The size and type of interleaver plays an important role in the performance  Turbo Code. Simulated for Turbo-Code interleaver structure variationsfor determining optimal interleaver in connection with determining the type ofinterleaverfor the mterleaver size and structure of the flat fading channel. In the simulation obtamed that the optimal interleaver turbo code on aflat fading channel can be achieved by using a type of random interleaver withframe size 384 to 20,738 bits.Key word: Turbo code, Interleaver, bit error rate,flat fading.